A Comprehensive Exploration of Java Man: Bio-Cultural Evolution from Homo erectus to Homo sapiens - Samuel J Haryono; Sri Utami; Restu Ambar Rahayuningsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
ABSTRACTAn overlap of time period between Homo erectus and Homo sapiens has not been confirmed. In the history of man, there have been two missing links: one between man and ape, and one between progressive Homo erectus and archaic Homo sapiens. Specimen dating on Java Man has been discrepant among research groups, and the use of molecular biology in ancient specimens has been a novelty. This study intends to use fossilised specimens, to harvest DNA to be sequenced for ribosomal DNA analysis for comparative phylogeny among ancient and modern man and other hominids. Dental calculus will be analysed to identify starch, carbohydrate, and protein to illustrate paleo dietary pattern. Soil samples will be examined for pollen and phytoliths to elaborate on ancient ecosystem. Blood samples will be procured from indigenous people along the riverflow region of Bengawan Solo to analyse modern human DNA. We hope that we may reconstruct the evolution pathway, construct the phylogenetic tree between ancient and modern hominids, and discover the uniqueness of Homo sapiens sapiens.Keywords: Java Man, Ribosomal DNA, Hominid Phylogenetic,